2013
DOI: 10.1007/s00442-013-2628-5
|View full text |Cite
|
Sign up to set email alerts
|

Arrival order among native plant functional groups does not affect invasibility of constructed dune communities

Abstract: Different arrival order scenarios of native functional groups to a site may influence both resource use during development and final community structure. Arrival order may then indirectly influence community resistance to invasion. We present a mesocosm experiment of constructed coastal dune communities that monitored biotic and abiotic responses to different arrival orders of native functional groups. Constructed communities were compared with unplanted mesocosms. We then simulated a single invasion event by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 46 publications
2
29
1
Order By: Relevance
“…Compared to T0, the average coverage of A. fruticosa during the study were higher in T1t1-T1t7, T3t8-T3t9 and T4t7-T4t9, but average height and ground diameter were lower in these plots, indicating that the individuals were smaller, but the number of individuals was higher when herbaceous species were sowed together. The result was consistent with the research by Mason et al (2013), which showed that ground cover was favorable for shrub germination but disadvantageous to growth. Moreover, when a field study was made in May 2014, it was observed that the stem number of each individual of A. fruticosa ranged from three to five in T0, but more than six in T1t9 and T4t9, which may partly account for the inconsistency between high coverage and low growth in these plots.…”
Section: The Effect Of Herbaceous Species On the Growth Of Shrubsupporting
confidence: 92%
“…Compared to T0, the average coverage of A. fruticosa during the study were higher in T1t1-T1t7, T3t8-T3t9 and T4t7-T4t9, but average height and ground diameter were lower in these plots, indicating that the individuals were smaller, but the number of individuals was higher when herbaceous species were sowed together. The result was consistent with the research by Mason et al (2013), which showed that ground cover was favorable for shrub germination but disadvantageous to growth. Moreover, when a field study was made in May 2014, it was observed that the stem number of each individual of A. fruticosa ranged from three to five in T0, but more than six in T1t9 and T4t9, which may partly account for the inconsistency between high coverage and low growth in these plots.…”
Section: The Effect Of Herbaceous Species On the Growth Of Shrubsupporting
confidence: 92%
“…At low densities, an invasive plant's competitive performance against well-established natives may be relatively weak if those native plants have priority access to limited resources and greater resource-use efficiency (e.g. Kardol et al 2013, Mason et al 2013. Ecosystems with high levels of resilience to disturbance (such as those with either persistent and dense seed banks or ones that are replenished often by immigrant propagules from adjacent patches of non-invaded vegetation) may have high impact thresholds.…”
Section: Ecological Framework For Invasive Species Impact Thresholdsmentioning
confidence: 99%
“…So far experiments manipulating plant species order of arrival have mainly used controlled experimental set-ups using pots or mesocosms (Ejrnæs et al, 2006; Chase, 2010; Moore and Franklin, 2011; Stevens and Fehmi, 2011; Dickson et al, 2012; Byun et al, 2013; Kardol et al, 2013; Mason et al, 2013; Ulrich and Perkins, 2014; Burkle and Belote, 2015; Wilsey et al, 2015; Sikes et al, 2016). Focusing on order of arrival of different PFGs, Körner et al (2008) set up an experiment with nine grassland species from three different groups (non-leguminous forbs, legumes, and grasses), sowing one group before the other two.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies testing priority effects by altering order of arrival compared effects of exotic and native competition both in the field (Chadwell and Engelhardt, 2008; Goldstein and Suding, 2014; Young et al, 2014; Vaughn and Young, 2015) and in controlled experiments (Grman and Suding, 2010; Stevens and Fehmi, 2011; Mason et al, 2013). These studies generally found that small differences in emergence timing can have long-lasting effects on community structure, and that initial control of exotics can increase the establishment of native perennial seedlings.…”
Section: Introductionmentioning
confidence: 99%